2003
DOI: 10.1097/00004728-200309000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Perfusion of Squamous Cell Carcinoma of the Upper Aerodigestive Tract

Abstract: We obtained baseline perfusion data for head and neck squamous cell cancers and compared it with adjacent normal structures. Our initial results suggest that CT perfusion parameters (CP, BF, BV, and MTT) can be used to help differentiate head and neck squamous cell carcinoma (SCCA) from adjacent normal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 9 publications
5
73
2
1
Order By: Relevance
“…11,18 Although the estimation of the CT-based first-pass tracer kinetic parameters like F in extacranial head and neck tumors has not been validated using a gold standard like radio-labeled H 2 O positron emission tomography (PET) imaging, the derived functional values in the initial studies [8][9][10] (which were the input parameter in our protocol) appear consistent with the tumor physiology in terms of increased cell proliferation and neoangiogenesis in order to satisfy the increased demand in blood supply. These phenomena result in elevated blood flow F (multiple abnormal low-resistance shunts of the newly formed vessels where the blood rapidly flows), elevated blood volume v 1 (as a measure of the tumor vasculature), and increased permeability-surface area product PS (due to immature newly formed vessels with increased fenestration which results in rapid extravasation of the contrast agent into the interstitial extracellular space).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,18 Although the estimation of the CT-based first-pass tracer kinetic parameters like F in extacranial head and neck tumors has not been validated using a gold standard like radio-labeled H 2 O positron emission tomography (PET) imaging, the derived functional values in the initial studies [8][9][10] (which were the input parameter in our protocol) appear consistent with the tumor physiology in terms of increased cell proliferation and neoangiogenesis in order to satisfy the increased demand in blood supply. These phenomena result in elevated blood flow F (multiple abnormal low-resistance shunts of the newly formed vessels where the blood rapidly flows), elevated blood volume v 1 (as a measure of the tumor vasculature), and increased permeability-surface area product PS (due to immature newly formed vessels with increased fenestration which results in rapid extravasation of the contrast agent into the interstitial extracellular space).…”
Section: Discussionmentioning
confidence: 99%
“…The parameter values used in this study were obtained from a previous study 8 in our institution after institutional review board approval and informed consent from the patients as well as from similar studies in literature. [9][10] These parameter values are F = 70 ml/min/100 g, v 1 = 5 ml/100 g, k 21 = 3.4 min −1 , and k 12 =0.85 min −1 , giving PS= 17 ml/min/100 g.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8] In particular, the necessity to detect early response to therapy and avoid any time delay in nonresponders has led to examining the predictive value of perfusion imaging, which might help in tailoring the therapy regimen on an individual basis. 9,10 Early proponents of perfusion studies have also demonstrated in a clinical setting that semi-or quantitatively estimated tumor perfusion might predict the outcome after definitive radiation therapy.…”
mentioning
confidence: 99%